2017
DOI: 10.1016/j.celrep.2017.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of an Actin-Based Filter in the Proximal Axon

Abstract: SUMMARY The essential organization of microtubules within neurons has been described, however, less is known about how neuronal actin is arranged and the functional implications of its arrangement. Here we describe in live cells an actin-based structure in the proximal axon that selectively prevents some proteins from entering the axon, while allowing the passage of others. Concentrated patches of actin in proximal axons are present shortly after axonal specification in rat and zebrafish neurons imaged live, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 29 publications
(48 reference statements)
3
51
0
Order By: Relevance
“…Several studies highlight the role of myosin as a tether, aiding in positioning of organelles along the neuronal process such as, at the axon initial segment (AIS), in axons and in dendrites. The AIS is an actin‐rich region that aids in halting dendritic cargo (Balasanyan et al, ; K. Watanabe et al, ). Specifically Myosin V motors present at the AIS cause stalling of dendritic cargo at the actin‐enriched AIS of neurons in culture (Al‐Bassam et al, ; Janssen et al, ) (Figure b).…”
Section: Actin In Organelle Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies highlight the role of myosin as a tether, aiding in positioning of organelles along the neuronal process such as, at the axon initial segment (AIS), in axons and in dendrites. The AIS is an actin‐rich region that aids in halting dendritic cargo (Balasanyan et al, ; K. Watanabe et al, ). Specifically Myosin V motors present at the AIS cause stalling of dendritic cargo at the actin‐enriched AIS of neurons in culture (Al‐Bassam et al, ; Janssen et al, ) (Figure b).…”
Section: Actin In Organelle Dockingmentioning
confidence: 99%
“…Several studies highlight the role of myosin as a tether, aiding in positioning of organelles along the neuronal process such as, at the axon initial segment (AIS), in axons and in dendrites. The AIS is an actin-rich region that aids in halting dendritic cargo (Balasanyan et al, 2017;K. Watanabe et al, 2012).…”
Section: Organelle Tethering By Myosin Motorsmentioning
confidence: 99%
“…Previous studies revealed that, in addition to sub-membranous actin rings, actin forms patches in the AIS (Balasanyan et al, 2017;D'Este et al, 2015;Janssen et al, 2017;Jones et al, 2014;Leterrier et al, 2015;Watanabe et al, 2012;Xu et al, 2013;Zhong et al, 2014) that may play a role in presynaptic terminals (D'Este et al, 2015) or in the filtering of vesicles carrying somatodendritic cargo (Balasanyan et al, 2017;Janssen et al, 2017;Watanabe et al, 2012). However, little is known about the dynamics and regulation of these actin patches.…”
Section: The Ais Contains Patches Of F-actin With a Low Rate Of Depolmentioning
confidence: 99%
“…Somatodendritic cargo entering the AIS halt at regions of high F-actin concentration, in a process that is dependent on myosin motors (Balasanyan et al, 2017;Janssen et al, 2017;Watanabe et al, 2012 . 6b).…”
Section: Tpm31 Is Necessary For Maintaining the Selectivity Of Axonamentioning
confidence: 99%
See 1 more Smart Citation